EFEK PERSEPSI HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. ALFA SCORPII BENGKONG BATAM - Silvia Revana Auzar, Silvia Revana Auzar (Zona Manajerial: Program Studi Manajemen (S1), 2019)
The purpose of this research was to get empirical evidence of the effects, of perception price, promotion and product quality at PT. Alfa Scorpii Bengkong partially and simultaneously. The range of variables of this research are price, promotion, and product quality. This research was using quantitative data which sourced from primary data that has been collected. The population in this research were the customers of PT. Alfa Scorpii Bengkong, as many as 125 customers, and sample as many as 95 customers. Collecting data was using questionnaire, hyphotesis testing was using multiple linear regression and T- Statistic test using SPSS software version 21.The result of first hyphotesis test showed that promotion, product quality has a significant effect on purchase decisions in PT Alfa Scorpii Bengkong, second hyphotesis test showed that quality of the product has an effect but not significant influence purchase decisions in PT Alfa Scorpii Bengkong, and third hyphotesis test showed that price have a significant effect on purchase decisions in PT Alfa Scorpii Bengkong.